Біонічно-орієнтований нейромережевий планувальник переміщення кіберфізичної системи у двовимірному просторі - Григоренко, Світлана Миколаївна; Протасова, Людмила Іванівна; Євсеєв, Олександр Володимирович; Hryhorenko, Svitlana; Protasova, Liudmyla; Yevseiev, Oleksandr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Метою роботи є розробка та формалізація біонічно-орієнтованого нейромережевого планувальника, здатного забезпечувати адаптивне та безпечне формування траєкторії руху в умовах невизначеного та динамічного середовища. Наукова новизна полягає у застосуванні концепції аферентного синтезу як механізму інтеграції сенсорної, навігаційної та цільової інформації. У роботі виконано формалізацію задачі планування переміщення, запропоновано структуру нейромережевого планувальника, обґрунтовано використання багатошарових і згорткових нейронних мереж. Отримані результати показують, що запропонований підхід забезпечує адаптивне та безпечне переміщення кіберфізичної системи, дозволяє уникати зіткнень із перешкодами та досягати цільової точки у реальному часі. Практична цінність роботи полягає у можливості застосування розробленого планувальника в інтелектуальних системах управління мобільними кіберфізичними об’єктами, зокрема в умовах динамічного та невизначеного середовища. /// EN: This paper presents a bionic-based approach to the synthesis of a neural network motion planner for a cyberphysical system operating in a two-dimensional space. The proposed method is grounded in the principles of afferent synthesis, which enable the integration of heterogeneous information, including sensory data, system state parameters, and target coordinates, into a unified decision-making framework. Such an approach allows the system to exhibit adaptive and goal-oriented behavior in environments characterized by uncertainty and dynamic changes. The motion planning problem is formalized as a nonlinear mapping from the input space, defined by lidarbased distance measurements, navigation data, and goal position, to the output space of control parameters. These parameters include the desired direction of motion, velocity, and additional control coefficients required for trajectory execution. The planner operates in real time, ensuring timely processing of incoming data and rapid response to environmental changes, including the appearance of dynamic obstacles. The architecture of the planner incorporates artificial neural networks as its computational core, with particular attention given to both multilayer feedforward networks and convolutional neural networks. Their applicability is justified by their ability to efficiently process high-dimensional sensory inputs and to generalize complex nonlinear dependencies between environmental states and control actions. The proposed approach enables safe navigation by preventing collisions and ensuring convergence to the target point within a finite time. It also provides a flexible framework for integrating autonomous and operator-driven control modes. The obtained results demonstrate the potential of combining bionic principles with neural network models for the development of intelligent motion planning systems in cyber-physical environments.
Bionic-based neural network motion planner for a cyber-physical system in a two-dimensional space
Keywords: аферентний синтез; біонічний підхід; кіберфізична система; нейромережевий плануваль- ник; планування переміщення; система технічного зору; штучні нейронні мережі; cyber-physical system; neural network planner; bionic approach; afferent synthesis; motion planning; artificial neural networks; vision system